Analisis Pengaruh Kinerja Keuangan Dalam Memprediksi Kondisi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) - B31112023, LIDIA SUNIARTI (Jurnal Manajemen Update, 2016)
Financial distress is a condition in which the company is facing problems financial difficulties. Companies that are experiencing financial difficulties are often difficult to pay off its obligations. The need for companies calculation of financial distress for the company to know the financial condition of the company and is expected to avoid such financial distress. The purpose of this study was to determine the effect of the liquidity ratio, profitability, financial leverage ratio and the ratio of the growth of the financial distress in companies manufacturing consumer goods industry sector listed in Indonesia Stock Exchange. Z-Score is used as a measure of financial distress. In this study, the sample company is a company manufacturing consumer goods industry sector listed in Indonesia Stock Exchange. By using purposive sampling method in a sample obtained 8 withdrawal consumer goods industry sector companies listed on the Indonesian Stock Exchange. The data analysis techniques used in this research is multiple regression analysis. In this study indicate that the liquidity ratio, profitability ratio, financial leverage ratios and growth rates have a significant effect on the financial distress. Thus the four variables can be a gauge to determine the company’s financial distress. Keywords: Financial Distress, Z-Score, Financial Performance, Financial Ratios and Financial Statements.